AR Improves Understanding of Germination Materials for Intellectual Disability Students in Special School 5th Grade - Meggy, Hendriano; Aprilia, Imas Diana (Journal of ICSAR, 2024)
This study aims to explore the use of AR technology to enhance the understanding of students with mild intellectual disabilities in the topic of germination processes in 5th Grade Special School Nusak Jagoi Babang. The research adopts an experimental method with a One Group Pretest-Posttest Design model. The research sample consists of 7 students from 5th Grade Special School. The study begins by conducting a pretest on the subjects before implementing the treatment, which involves the use of AR technology. After the subjects receive the treatment, a posttest is conducted to measure their learning improvement. The results of the study indicate that the use of AR technology can enhance the understanding of students with mild intellectual disabilities in the topic of germination processes. This summary concludes by emphasizing the importance of utilizing AR technology to improve the understanding of students with mild intellectual disabilities in the topic of germination processes, which can serve as a reference for developing technology-based learning programs in the future.